Regulatory Gaps in Islamic Donation-Based Crowdfunding (IDCF) Platforms in Malaysia from Project Managers’ Perspective - Syifa’ Mawaddah Zaimi; Muhammad Iqmal Hisham Kamaruddin; Nurul Aini Muhamed; Wan Nur Fazni Wan Mohamad Nazarie; Aimi Fadzirul Kamarubahrin; Rafisah Mat Radzi (Human Resource Management Academic Research Society, 2025)
Indexed